PENGAWASAN PIUTANG SEBAGAI SARANA MENGHINDARI PENYELEWENGAN PADA PT. RAZZA PRIMA TRAFO - Ratih Anggraini Siregar (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2020)
The purpose of this research is to know the extent of the supervision of receivables at PT. Razza Prima Trafo in the implementation of the company's activities in avoiding fraud. The results of the research are for services companies such as PT. Razza Prima Trafo, receivables are the most important and dominant elements, besides receivables is the heart of the company. So PT. Razza Prima Trafo Set specifically the supervision of the company's receivables. The supervision of good and adequate receivables will ensure the smooth flow of receivables as cash. Research conclusion is a credit sales procedure has been designed by meeting effective internal supervision requirements, the authority of the transaction related to the trade receivables is done by PT. Razza Prima Trafo precisely and appropriately, and PT. Razza Prima Trafo has documented all transactions related to trade receivables and has a record of sertalaporan that help the management of the decision on the problems relating to the trade receivables.